Environmental friendly solar car / Ahmad Faeiz Mohd Ropei & Mohammad Amirul Ikhwan Hashim - Mohd Ropei, Ahmad Faeiz; Hashim, Mohammad Amirul Ikhwan (2015)
Nowadays, many people are busy doing their work and does not have a time to take care of their flower plant. Thus the plant will lack of water. The plant will be wilted and the growth will be stunted. So we comes out with an idea to create a device that can ease the care of the flower plant and eventually can enhance the growth of the flower plant. This device can water the plant at a specific time without human interference at all. After all this device also emitted light to the plant at night in order to help the plant growth faster. We hope that the invention of this device can help the people out there to take care of their flower plant and thus create a fresh and greener environment